Analysis of the Motivation of Junior Handball Players in Hungary - Krupánszki, Kornél; Peter, Karacsony; Krupánszki, Kíra (Acta Carolus Robertus, 2023)
Handball is one of the most popular sports in Hungary. However, little research has been done on the motivation of young athletes. The present study analysed the motivation of young handball players in Hungary in 2022. The aim of the research was to assess the motivation of young athletes and their relationship with their coach. A total of 190 responses were returned during the quantitative research. The age groups surveyed had no effect on the coach’s results orientation. Among the new findings, we also highlight that handball divisions do not influence the young athlete in terms of the individual benefits of the sport. Coaches have a major role in maintaining the motivation of young athletes and therefore need to pay particular attention to this in their daily activities.